Cyclic Oxygen Release Characteristics of Bifunctional Copper Oxide/Calcium Oxide Composites. Issue 10 (4th May 2016) - Duan, Lunbo; Godino, Danilo; Manovic, Vasilije; Montagnaro, Fabio; Anthony, Edward J.
Abstract: Integrated calcium–copper (Ca–Cu) looping is a novel carbon capture technology that uses copper oxide to transport oxygen and calcium oxide to capture CO2 in the same process. Investigations into the oxygen release behavior of the bifunctional CuO/CaO composite are critical to assess the potential for applying this technology to solid fuels such as coal. In this study, three different CuO/CaO composites having different relative percentages (CuO75CaO25, CuO50CaO50, and CuO25CaO75) were manufactured in a commercial granulator and then tested in a bubbling fluidized bed reactor to examine their oxygen release characteristics at temperatures in the 880–940 °C range. All the composites exhibited clear oxygen release properties during the testing, indicating that the solid fuel can be directly oxidized rather than being gasified first in the Ca–Cu looping process. At the same temperature, the oxygen release rate of CuO25CaO75 is the fastest and its final oxygen yield is the largest, followed by CuO75CuO25 and CuO50CaO50. XRD results reveal that Ca2 CuO3 is formed in the used samples of CuO75CuO25 and CuO50CaO50, but not in the case of CuO25CaO75, which may explain the performance difference observed. Further examination of the attrition and agglomeration behavior shows that all the composites are stable and strong, and it appears that CuO25CaO75 is the most stable and strongest of the materials examined. Abstract : Coming up for air : Integrated calcium–copper (Ca–Cu) looping is a novel carbon capture technology that uses copper oxide to transport oxygen and calcium oxide to capture CO2 in the same process. Clear and stable oxygen release occurs for a range of CuO/CaO composites tested at temperatures in the 880–920 °C range. The steady‐state oxygen concentration increases with the temperature. CuO25CaO75 shows the highest oxygen concentration and final oxygen yield.